Doing and being an interpretation of Aristotle's Metaphysics Theta - Beere, Jonathan B., 1974- (Oxford : Oxford University Press, 2009)
'Doing and Being' confronts the problem of how to understand two central concepts of Aristotle's philosophy: energeia and dunamis. These terms seem ambiguous between actuality/potentiality and activity/capacity, but Aristotle did not intend this.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aristotle